Durable superhydrophobic Zn/ZnO/TiO2 surfaces on Ti6Al4V substrate with self-cleaning property and switchable wettability. Issue 1 (January 2018) - He, Ge; Lu, Shixiang; Xu, Wenguo; Yu, Tianlong; Li, Jingyan; Dai, Tanlong
Abstract: Durable superhydrophobic (SHP) Zn/ZnO/TiO2 surfaces with dendritic structures on Ti6 Al4 V substrate were obtained by chemical etching, electrodeposition and following annealing process. The resultant coatings electrodeposited at −1.5 V for 10 min and annealed at 190 °C for 60 min showed fine superhydrophobicity with a water contact angle of 160° and a rolling angle less than 1°, showing excellent rolling-off and self-cleaning properties. The morphology, chemical components and growth mechanism of samples were investigated by scanning electron microscopy (SEM), X-ray diffraction pattern (XRD), Energy-dispersive spectroscopy (EDS) and X-ray photoelectron spectroscopy (XPS). Surface tribological properties were characterized by a universal mechanical tester (UMT). The as-prepared Zn/ZnO/TiO2 surface still kept excellent SHP stability after exposure to the air, buried in soil and cold storage at 5 °C in the fridge for one year, as well as excellent repellence to some daily-used liquids such as coke, coffee, red wine, milk and tea. The surface can be reversibly switched between superhydrophobicity and superhydrophilicity by alternating UV illumination and dark storage or heating, which offer possibilities to widen future applications.